2001 IEEE Nuclear Science Symposium Conference Record (Cat. No.01CH37310)
DOI: 10.1109/nssmic.2001.1008684
|View full text |Cite
|
Sign up to set email alerts
|

HeinzelCluster: accelerated reconstruction for FORE and OSEM3D

Abstract: We have investigated two strategies to speedup reconstruction of data from our high resolution PET scanner (HRRT) on a dedicated cluster (7 nodes with 4 PIII Xeon@700 MHz, switched Fast Ethernet and Myrinet networking, Windows NT). With the first strategy, FORE/FOREJ and a fast 2D reconstruction method, we were able to reduce the 2D reconstruction time from 38 minutes to approx. 100 seconds. The second approach was to accelerate OSEM3D with a two-stage parallelization scheme resulting in a drop of reconstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…For each subject, MRI data were coregistered to the summed 18 F-DPA-714 image (0.3-24 min) using VINCI software (11). Regional time-activity curves were extracted using PVELab software (12), in which the Hammers template (13) was projected onto the coregistered MRI scan and subsequently applied to the dynamic 18 F-DPA-714 scan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For each subject, MRI data were coregistered to the summed 18 F-DPA-714 image (0.3-24 min) using VINCI software (11). Regional time-activity curves were extracted using PVELab software (12), in which the Hammers template (13) was projected onto the coregistered MRI scan and subsequently applied to the dynamic 18 F-DPA-714 scan.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-labeled N,N-diethyl-2-(2-[4-(2-fluoroethoxy)phenyl]-5,7-dimethylpyrazolo[1,5-a]pyrimidine-3-yl)acetamide (DPA-714) is a PET ligand with high specificity for TSPO. Early studies showed that 18 F-DPA-714 had better bioavailability (4), lower nonspecific binding, and higher nondisplaceable binding potential (BP ND ) than 11 C-DPA-713 (5). It is considered to be superior to 11 C-PK11195 (6-9) in specificity, and hence, it could be a potential tracer for assessing the early stages of AD.…”
mentioning
confidence: 99%
“…To increase the signal-to-noise ratio and enable efficient reconstruction of the cortical sheet, each pair of individual MR acquisitions was averaged after coregistration (19). For coregistration, MR images were skull-stripped using the Brain Extraction Tool ([BET], part of the FMRIB software library [FSL]; http:// www.fmrib.ox.ac.uk/fsl) (20).…”
Section: Methodsmentioning
confidence: 99%
“…In their work, Shattuck et al [106] describe a parallel implementation of the MAP-PCG reconstruction [26] using a masterslave model with 9 dual PC nodes. The work of Vollmar [107] describes a parallel extension of the OSEM3D reconstruction [92] and is also using a masterslave model with 7 quad PC nodes. By calculating the system matrix on the fly and neglecting the physics of the detection system these authors could handle very large reconstruction problems on the HRRT.…”
Section: Parallel Implementation Of Iterative Reconstructionmentioning
confidence: 99%